A Polyhydroxyalkanoates-Based Carrier Platform of Bioactive Substances for Therapeutic Applications - Zhang, Xu; Liu, Xin-Yi; Yang, Hao; Chen, Jiang-Nan; Lin, Ying; Han, Shuang-Yan; Cao, Qian; Zeng, Han-Shi; Ye, Jian-Wen (Frontiers in Bioengineering and Biotechnology, 2022)
Bioactive substances (BAS), such as small molecule drugs, proteins, RNA, cells, etc., play a vital role in many therapeutic applications, especially in tissue repair and regeneration. However, the therapeutic effect is still a challenge due to the uncontrollable release and instable physico-chemical properties of bioactive components. To address this, many biodegradable carrier systems of micro-nano structures have been rapidly developed based on different biocompatible polymers including polyhydroxyalkanoates (PHA), the microbial synthesized polyesters, to provide load protection and controlled-release of BAS. We herein highlight the developments of PHA-based carrier systems in recent therapeutic studies, and give an overview of its prospective applications in various disease treatments. Specifically, the biosynthesis and material properties of diverse PHA polymers, designs and fabrication of micro- and nano-structure PHA particles, as well as therapeutic studies based on PHA particles, are summarized to give a comprehensive landscape of PHA-based BAS carriers and applications thereof. Moreover, recent efforts focusing on novel-type BAS nano-carriers, the functionalized self-assembled PHA granules in vivo, was discussed in this review, proposing the underlying innovations of designs and fabrications of PHA-based BAS carriers powered by synthetic biology. This review outlines a promising and applicable BAS carrier platform of novelty based on PHA particles for different medical uses.